Gauteng medical orthotist prosthetists perceptions about self-screening to detect adolescent idiopathic scoliosis : a qualitative exploration - Snyman, Courtney (Stellenbosch : Stellenbosch University, 2021)
Thesis (MHumanRehabSt)--Stellenbosch University, 2021.